Budgetary decision-making practices and styles of college presidents: the case of historically black Colleges and Universities - Dumas, Brandon K.; Chanika, Jones; Mbarika, Victior; Kituyi, Geoffrey M. (The Electronic Journal of Information Systems in Developing Countries, 2014)
Historically Black Colleges and Universities are seeking to reposition themselves in the current environment of higher education. This requires the ability to select leaders who have a firm understanding of planning, budgeting and knowing how to manage and promote their institutions. However, little data exists on the role played by college presidents in budgetary process and how their decision-making and leadership styles influence budgeting. This paper presents initial insights into the role played by of college presidents in budgeting. Study participants consisted of sitting and former presidents of Historically Black Colleges and Universities from four-year public and private colleges and universities in the United States of America, who had at least two years of experience as president. A total of 17 presidents participated in the interviews. Data were analyzed and presented qualitatively. Findings reveal that the main role of college presidents was approval of final budgets. They did not directly participate in process of budgeting and were at large receivers of budgetary information rather than givers. Most of the budgetary work was done by individual departments, sections, directorates, schools and faculties who generated their own budgets and passed them to higher authorities for approval. The study posts that for effective budgeting, college presidents should play a bigger role in terms of indentifying strategic avenues of new revenues for their colleges and at the same time try to find new cost effective ways of doing business for example through adoption of technology.
Keywords: Budgetary Decision-Making; Decision-Making practices; Decision-Making styles; College Presidents; Historically Black Colleges and Universities